2005
DOI: 10.1002/cncr.21246
|View full text |Cite
|
Sign up to set email alerts
|

Promoting adjustment after treatment for cancer

Abstract: The transition from the period of diagnosis and medical treatment of cancer to survivorship (i.e., the reentry phase) is an understudied phase in the cancer trajectory. The objectives of this report were 1) to illustrate several adaptive tasks of the reentry phase, 2) to provide examples of research on factors that predict positive adjustment during this phase, and 3) to discuss interventions that address the adaptive tasks of early cancer survivorship. Although the pertinent empirical literature is scarce, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
157
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 183 publications
(167 citation statements)
references
References 42 publications
8
157
0
2
Order By: Relevance
“…Patients experience a significant disruption in their global functioning and supportive care needs immediately following diagnosis however they continue to require assistance adapting to and coping with their cancer throughout the cancer trajectory [23,37]. Stanton et al [23] suggest that the realisation one has cancer may only become apparent over time, for example, when active coping strategies (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients experience a significant disruption in their global functioning and supportive care needs immediately following diagnosis however they continue to require assistance adapting to and coping with their cancer throughout the cancer trajectory [23,37]. Stanton et al [23] suggest that the realisation one has cancer may only become apparent over time, for example, when active coping strategies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The change in care and support following treatment completion suggests that patient satisfaction and social support may be the important predictors of unmet supportive care needs over time. At the conclusion of treatment, medical care and support may decrease owing to the belief that the worst is over and that the patient does not require ongoing assistance [23]. Patients indicate some discomfort requesting information from medical providers as time since diagnosis increases and instead seek information from popular media [24].…”
mentioning
confidence: 99%
“…First, women are still contending with the physical effects of treatment, including fatigue, hair loss, early menopausal symptoms, lymphoedema, and decreased libido. Many women become distressed because they had not anticipated ongoing treatment-related problems (Beisecker et al, 1997;Stanton et al, 2005). Second, cancer survivors no longer need to focus intensely on medical treatment, leaving room for a psychological struggle (Schnipper, 2001).…”
mentioning
confidence: 99%
“…Interviews with breast cancer survivors after the end of treatment revealed that women were just beginning to reflect on fears and existential issues at this time (Lethborg et al, 2000). Third, loss of support from family and friends who may not realise that cancer survivors continued to struggle with cancer-related physical and psychological issues is another potential source of distress (Stanton et al, 2005). The loss of regular contact with health-care providers may also result in feelings of decreased support (Lethborg et al, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation